Angola : Recent Economic Developments. (IMF Staff Country Reports; Country Report ;, 2000)
Economic activity and social conditions have been adversely affected by the intensification of the civil war. The goal is to restore domestic and external equilibrium and create the conditions for sustained growth, especially by boosting the growth of the non-oil sectors, lowering inflation to single-digit rates, improving the efficiency and transparency of public sector operations, and enhancing the role of the private sector. In March 1999, the government launched an adjustment and reform program. The authorities have made adjustments in fuel prices and electricity tariffs.